ON THE PROBLEM OF PREPARING CHILDREN WITH DISABILITIES FOR FAMILY LIFE (Archive of Conferences, 2021)
The article describes the legal and scientific basis for the preparation of children with disabilities for family life, the pedagogical and psychological features of the preparation of children with disabilities for family life.